# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+\lambda y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y^{\prime \prime }+\frac {\lambda y}{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y^{\prime \prime }+\frac {\lambda y}{x} = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+\left (x^{2}+1\right ) y^{\prime \prime }+\frac {\lambda y}{x^{2}+1} = 0
\] |
✓ |
✓ |
|
\[
{}-\frac {6 y^{\prime } x}{\left (3 x^{2}+1\right )^{2}}+\frac {y^{\prime \prime }}{3 x^{2}+1}+\lambda \left (3 x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x^{4} x^{\prime }-x^{\prime }+x = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }+x^{\prime }+{x^{\prime }}^{3}+x = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }+\left (x^{4}+x^{2}\right ) x^{\prime }+x^{3}+x = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }+\left (5 x^{4}-6 x^{2}\right ) x^{\prime }+x^{3} = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }+\left (x^{2}+1\right ) x^{\prime }+x^{3} = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }-3 x^{\prime }+2 x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}z^{\prime \prime }-4 z^{\prime }+13 z = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\theta ^{\prime \prime }+4 \theta = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}2 z^{\prime \prime }+7 z^{\prime }-4 z = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+10 x = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{\prime \prime }-20 x^{\prime }+21 x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\omega ^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x = t^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime } = t^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x^{\prime }-2 x = 3 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x^{\prime }-2 x = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+x = {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\omega ^{2} x = \sin \left (\alpha t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\omega ^{2} x = \sin \left (\omega t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+10 x = {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+10 x = {\mathrm e}^{-t} \cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+10 x = {\mathrm e}^{-2 t} \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+4 x = {\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x^{\prime }-2 x = 12 \,{\mathrm e}^{-t}-6 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = 289 t \,{\mathrm e}^{t} \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\omega ^{2} x = \cos \left (\alpha t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\omega ^{2} x = \cos \left (\omega t \right )
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-\left (t^{2}+2 t \right ) y^{\prime }+\left (2+t \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (\cos \left (t \right ) t -\sin \left (t \right )\right ) x^{\prime \prime }-x^{\prime } t \sin \left (t \right )-x \sin \left (t \right ) = 0
\] |
✗ |
✗ |
|
\[
{}\left (-t^{2}+t \right ) x^{\prime \prime }+\left (-t^{2}+2\right ) x^{\prime }+\left (2-t \right ) x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\tan \left (t \right ) x^{\prime \prime }-3 x^{\prime }+\left (\tan \left (t \right )+3 \cot \left (t \right )\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-6 y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-x = \frac {1}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \cot \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }-2 x = t^{3}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime } = \tan \left (t \right )
\] |
✓ |
✓ |
|
\[
{}\left (\tan \left (x \right )^{2}-1\right ) y^{\prime \prime }-4 \tan \left (x \right )^{3} y^{\prime }+2 y \sec \left (x \right )^{4} = \left (\tan \left (x \right )^{2}-1\right ) \left (1-2 \sin \left (x \right )^{2}\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }-5 t x^{\prime }+10 x = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+t x^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} z^{\prime \prime }+3 x z^{\prime }+4 z = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}4 t^{2} x^{\prime \prime }+8 t x^{\prime }+5 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} z^{\prime \prime }+5 x z^{\prime }-z = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime \prime }+3 t x^{\prime }+13 x = 0
\] |
✓ |
✓ |
|
\[
{}a y^{\prime \prime }+\left (b -a \right ) y^{\prime }+c y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+10 y = 100
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \sin \left (t \right )-\cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \frac {1}{\sin \left (x \right )^{3}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \cosh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {2 {y^{\prime }}^{2}}{1-y} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime }+4 x = {\mathrm e}^{t}+{\mathrm e}^{2 t}+1
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} x^{\prime \prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (9 x^{2}-\frac {1}{25}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+{y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 3 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 1-\frac {1}{\sin \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}u^{\prime \prime }+\frac {2 u^{\prime }}{r} = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = \frac {y y^{\prime }}{\sqrt {x^{2}+1}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } y^{\prime \prime } = {y^{\prime }}^{3}+{y^{\prime \prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = t \sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = \sinh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+2 y = x \,{\mathrm e}^{x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }-6 y = 1
\] |
✓ |
✓ |
|
\[
{}m x^{\prime \prime } = f \left (x\right )
\] |
✓ |
✓ |
|
\[
{}m x^{\prime \prime } = f \left (x^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right )^{2} y^{\prime \prime }+\left (1+x \right ) y^{\prime }+y = 2 \cos \left (\ln \left (1+x \right )\right )
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{3}+y^{\prime \prime }+1 = x
\] |
✗ |
✓ |
|
\[
{}x^{\prime \prime }+10 x^{\prime }+25 x = 2^{t}+t \,{\mathrm e}^{-5 t}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime \prime }-x {y^{\prime }}^{2}-y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = y^{\prime } \ln \left (\frac {y^{\prime }}{x}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (3 x \right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y^{3}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }-{y^{\prime }}^{2} = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+3 y^{\prime }+4 x^{2} y = 1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-y = \sin \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = x^{2}+y
\] |
✓ |
✓ |
|
\[
{}\sinh \left (x \right ) {y^{\prime }}^{2}+y^{\prime \prime } = x y
\] |
✗ |
✗ |
|